Design of Spreading-Codes-Assisted Active Imaging System. (1st July 2015) - Volkov, Alexey; Žganec Gros, Jerneja; Žganec, Mario; Žganec, Mario; Javornik, Tomaž; Aleš, Švigelj
This work discusses an innovative approach to imaging which can improve the robustness of existing active-range measurement methods and potentially enhance their use in a variety of outdoor applications. By merging a proven modulation technique from the domain of spread-spectrum communications with the bleeding-edge CMOS sensor technology, the prototype of the modulated range sensor is designed and evaluated. A suitable set of application-specific spreading codes is proposed, evaluated and tested on the prototype. Experimental results show that the introduced modulation technique significantly reduces the impacts of environmental factors such as sunlight and external light sources, as well as mutual interference of identical devices. The proposed approach can be considered as a promising basis for a new generation of robust and cost-efficient range-sensing solutions for automotive applications, autonomous vehicles or robots.